THE FORM OF STATE DEFENSE AWARENESS THROUGH COMMUNITY PARTICIPATION CULTURE IN RENEWABLE ENERGY MANAGEMENT - Khotimah, Khusnul (Jurnal Pertahanan & Bela Negara, 2018)
Each country has a unique personality that becomes the country's identity. Indonesia is known as a country that has community participation culture. However, that identity has been fading amid globalization today. As a matter of fact, community participation culture has the potential to be the unique culture of Indonesia in conquering the world through the conscious choice to defend the country for the unity of the nation. Research method employed in this study is literature review and observation based on author’s previous research. The result is analysis for the application of community participation culture in the management of renewable energy towards energy independence reinforcing state defense through the implementation of the basic principles of community participation which includes: (1) community develops, provides and utilizes renewable energy sources together; (2) community becomes the pioneer and innovator that can facilitate other community in independently providing and propelling the growth of people’s economy to reinforce state defense. Renewable energy management through state participation should not only be a normative advice, but should be clearly regulated to ensure people’s active participation in achieving the 23% target for renewable energy mix in 2025. There is a need to optimize the sustainable coordination, evaluation and supervision between Ministry of Energy and Mineral Resources, Ministry of Village, Development of Disadvantaged Regions and Transmigration as well as Ministry of Defense in order to ensure people’s participation in creating sustainable renewable energy management and as a form of defending the state.Keywords: defending the state, renewable energy, community participation culture